Microbial phenolic metabolites are associated with better frontal lobe cognition - Inés Domínguez-López; Isabella Parilli-Moser; Anna Vallverdú-Queralt; Anna Tresserra-Rimbau; Cinta Valls-Pedret; Zenaida Vázquez-Ruiz; Olga Castañer; Ramon Estruch; Emili Ros; Rosa M. Lamuela-Raventós (Food Science and Human Wellness)
With increasing life expectancy, neurodegenerative diseases have become one of the leading causes of ill-health in the elderly. Preventive strategies include following healthy diets, such as the Mediterranean diet, which is particularly rich in polyphenols, bioactive compounds with neuroprotective properties. The aim of this study was to assess the association of microbial phenolic metabolites (MPM) with cognition. This cross-sectional analysis was performed with 200 participants of the PREDIMED trial (Barcelona-Clinic recruitment center). A novel method based on liquid chromatography coupled to mass spectrometry was used to identify urinary MPM (protocatechuic acid, enterodiol glucuronide, enterolactone glucuronide, urolithin B glucuronide, and vanillic acid glucuronide), and cognitive function was evaluated with neuropsychological tests. Multivariable-adjusted ordinary least squares regression was used to assess the associations between cognitive function and MPM, and a score was calculated as the weighted sum of MPM. A higher MPM score was associated with better frontal lobe function. Among individual metabolites, vanillic acid glucuronide was correlated with frontal cognitive performance. Participants with higher concentrations of vanillic acid glucuronide and urolithin B glucuronide obtained better scores in the Color Trail Test part 2. A higher score for urinary multi-MPM was associated with better frontal cognitive performance in an older Mediterranean population.